2023
DOI: 10.1371/journal.ppat.1011262
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism causes changes in caterpillar odours and associated bacterial communities with consequences for host-location by a hyperparasitoid

Abstract: Microorganisms living in and on macroorganisms may produce microbial volatile compounds (mVOCs) that characterise organismal odours. The mVOCs might thereby provide a reliable cue to carnivorous enemies in locating their host or prey. Parasitism by parasitoid wasps might alter the microbiome of their caterpillar host, affecting organismal odours and interactions with insects of higher trophic levels such as hyperparasitoids. Hyperparasitoids parasitise larvae or pupae of parasitoids, which are often concealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 87 publications
(170 reference statements)
0
4
0
Order By: Relevance
“…Previous studies reported increase in specific abundances and/or acquisition of new host gut microbial members after parasitization due to transfer of microbes from the parasitoid to the host, [ 1 , 8 , 15 ]. In this study, we found a similar trend in the parasitized larval guts which comprised Weisella and Pantoea species, bacteria that were not present in the control larvae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported increase in specific abundances and/or acquisition of new host gut microbial members after parasitization due to transfer of microbes from the parasitoid to the host, [ 1 , 8 , 15 ]. In this study, we found a similar trend in the parasitized larval guts which comprised Weisella and Pantoea species, bacteria that were not present in the control larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Microbes have emerged as key drivers of host-natural enemy interactions of several horticultural insect pests, often shaping the evolutionary aspects of these bi-partite models. This is primarily through regulating semiochemical production and release, nutrient metabolism, immune function, development, adult size, and other host fitness traits [ 1 4 ]. Hence, understanding the dynamics and regulatory patterns of microbial communities is crucial to deciphering the ecological functioning of insect pests, especially with their natural enemies, such as parasitoid wasps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, numerous hymenopteran wasps utilize mVOCs from their prey or the surrounding environment to locate food sources for their offspring [ 24 ]. For instance, the hyperparasitoid enemies of parasitic wasps can reliably use the odors of parasitized caterpillars to find the parasitic wasp larvae developing inside the caterpillar [ 28 ]. The mVOCs emitted by certain fungi facilitate host localization over long distances, whereas bacteria and yeasts may contribute to short-distance localization [ 29 ].…”
Section: Introductionmentioning
confidence: 99%